Employee Performance at the Sukoharjo Primary Tax Service Office - Bramudya Alfa Arnanda; Istiatin; Sudarwati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research is included in the type of quantitative descriptive research. In this study, the relationships or influences studied include job rotation, career development, organizational commitment, and performance appraisals on employee performance at the Sukoharjo Pratama Tax Service Office. The place where this research was carried out was in the Sukoharjo Pratama Tax Service Office. The time used by researchers for this research was carried out from the date of issuance of the research permit within a period of approximately 6 (six) months, namely July to December 2024. The population that will be used as research is ASN employees in the Sukoharjo Pratama Tax Service Office environment, totaling 110 employees. This study uses a saturated sampling method so that the sample taken is 110 employees with ASN status. in this study using two variables, namely the independent variable and the dependent variable. The two variables are the Independent Variable The variables taken are Job Rotation, Career Development, Organizational Commitment, and Work Performance Assessment (X) in addition to the Dependent Variable: Employee Performance (Y). The data obtained inThis research is then processed using multiple linear regression analysis tools. Based on the results of data analysis and hypothesis testing that have been carried out, it shows that Job rotation, Career development, Organizational commitment, Performance appraisal have a significant effect on employee performance at the Pratama Sukoharjo Tax Service Office. Keywords: Employee Performance, Job Rotation, Career Development, Organizational Commitment, and Job Performance Assessment